LEXICAL MEANS OF CREATING THE IMAGE OF THE 2022 OLYMPIC GAMES IN BEIJING IN RUSSIAN NEW MEDIA - Lonskaya, A.Yu.; Burskaya, E.A.; Karpukhina, N.M.; Panova, L.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify the characteristic lexical means that form the actual image of the 2022 Olympic Games in Beijing in the new Russian media. Methods and structure of the study. In the course of scientific work, an analysis was made of the Russian websites of the newspapers «Izvestia» and «Arguments and Facts», which are included in the «Top 10 Russian Media - January 2022» (according to the Medialogy website). In total, 100 articles on the Beijing 2022 Olympics were analyzed, complex analysis, linguocultural analysis, descriptive and comparative methods, observation and classification methods were used. Results and conclusions. An analysis of the texts of new media dedicated to the 2022 Olympic competitions allows us to conclude that rhetorical figures predominate in them, including pun (38% of the total volume of the analyzed vocabulary) and metaphor (33%), as well as vernacular and colloquial lexical units (28% ), which are distinguished by anorativity in the field of vocabulary, which, in turn, brings vivid expression and expressiveness to the text. The image of the Olympic Games is made up of lexical expressive means that have a strong connection with the linguistic culture of readers: puns have a comic basis, which attracts the reader's attention; metaphors with mega-spheres-sources "medicine", "theater", "war" allow you to create an image based on the conceptual system of a person; colloquial and colloquial lexical units contribute to the formation of the most relevant and accessible image of the 2022 Olympics.